Reimagining the future of a business education program using appreciative inquiry - Barcelona, Alvin; Caminong, Joliber; dela Cruz, Sam Rhoy B. (Institute of Advanced Engineering and Science, 2023)
Rethinking the future of education has fueled momentum for large-scale change after the significant effects of the global pandemic. This momentum for change may require large amounts of positive affect by affirming and appreciating what works well during difficult times rather than identifying and understanding problematic areas. This study made use of appreciative inquiry in reimagining the future of a Business Education program in a private tertiary institution in the Philippines. Using naturalistic approach, 35 business education students and three teachers were interviewed using positive questions that amplify the positive core of the college. The participants unleashed the strengths of the college such as the implemented flexible modular setup, availability of the repository of educational resources, efficient communication during online learning, empowered student council, and group collaborations. Through inquiry and dialogue, participants co-created the reimagined future of the College of Business Administration which is a more flexible and inclusive means of delivering the Business Education Curriculum and upgraded and holistic learning experiences for the learners. Through the use of appreciative inquiry, the participants collectively leveraged the best practices of the college and their envisioned future to design high-impact strategies that can move the college decisively to its reimagined future.